Examination of Over-Discharge Effects on a Cylindrical Lithium-Ion Battery via the Immersion of a Copper Strip in a Salt Solution - Bayarmaa Tserendejid; Erdenebold Urtnasan; Jei-Pil Wang (Corrosion and Materials Degradation, 2025)
Li-ion battery recycling is growing with better tech and eco-awareness. Explosions are possible during battery recycling due to their residual voltage. Proper battery discharge is vital to successful recycling. The goal of this study was to investigate a new method for discharging cylindrical batteries, utilizing a saltwater solution and copper conductors and analyzing the impact of both direct and indirect contact between the copper and the battery. A key variable impacting the discharge process was inconsistent spacing between the battery and the copper conductor. In the gap, the saltwater, functioning as an electrolyte solution, created an electrical short circuit, thus causing faster discharge. Because the battery was not in contact with the copper conductor during the discharge process, corrosion of the battery cap and valve occurred, leading to the battery’s anode and cathode elements dissolving into the solution. However, a near-total voltage drop of 99% was observed in the battery, indicating that it was almost completely discharged. Upon making contact with the copper strip during its discharge cycle, the battery exhibited no signs of corrosion. This report details the battery discharge process, encompassing an analysis of the electrochemical reaction, schematic diagrams, and a chemical analysis of the discharge precipitate.